The Legal Problems on Occupational Accidents Insurance Policy for State Civil Apparatus - Gerson Oktavian, Ariel; Susila Wibawa, Kadek Cahya; Sonhaji, Sonhaji (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 11 No 2 (2022), 2022)
Initially, Employment and social protection was based on National Social Security System Law and it is applied for public, includingState Civil Apparatus. According to the law, all employment social security should be implemented by Social Security Administration of Employment. Legal problems then emerged as a result of the stipulation of occupational accident insurance rules for State Civil Apparatus that were managed by PT Taspen as mandated by Government Regulation No. 70/2015. This research aimed to describe and analyze the legal construction of Occupational Accident Security and Death Security regulations for State Civil Apparatus.  This research uses doctrinal legal research as part of qualitative research with conceptual and statue approach. The analysis was carried out descriptively by processing primary legal materials, secondary legal materials, and tertiary legal materials. The results of the research showed that legal problems were in the form of disharmony and regulatory inefficiency in the Occupational Accident Security and Death Security policies. A clash occurred between the State Civil Apparatus Law, the Social Security Administration Law and Government Regulation No. 70/2015. The problems occurred were related to the authority of PT Taspen as the organizer of Occupational Accident Security and Death Security for State Civil Apparatus as well as violations of the National Social Security System principles in the management of Occupational Accident Security and Death Security for ASN based on Government Regulation No. 70/2015.